Augmented reality Mathematics media for enhancing critical thinking and motivation in elementary students - Umahati Fatmaningrum; Akhmad Jazuli (Curricula: Journal of Curriculum Development, 2025)
The rapid advancement of information and communication technology in the digital era has transformed many sectors, including education. In line with Society 5.0 demands, education is expected to integrate technology into learning to foster students' critical thinking and motivation. This study aims to develop Augmented Reality (AR)-based Mathematics learning media using the Assemblr EDU application to enhance elementary students’ critical thinking and motivation. The research employed the Research and Development (R&D) method, utilizing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through interviews, questionnaires, and tests. The media’s effectiveness was tested using a quasi-experimental design with a non-equivalent control group. Results show that AR-based Mathematics media are technically and pedagogically valid and effectively improve students’ critical thinking and motivation. Expert validation confirmed its feasibility with minor revisions, and effectiveness testing showed significant advantages over conventional methods. AR enables interactive visualization of spatial concepts, supports concept identification and clarification, and creates an engaging learning experience. In conclusion, integrating AR technology into Mathematics learning offers an innovative solution to enhance numeracy literacy and meet 21st-century learning challenges in elementary schools.   Abstrak Kemajuan pesat teknologi informasi dan komunikasi di era digital telah mentransformasi berbagai sektor, termasuk pendidikan. Sejalan dengan tuntutan Society 5.0, dunia pendidikan dituntut untuk mengintegrasikan teknologi dalam proses pembelajaran guna mendorong kemampuan berpikir kritis dan motivasi belajar peserta didik. Penelitian ini bertujuan mengembangkan media pembelajaran matematika berbasis Augmented Reality (AR) menggunakan aplikasi Assembler EDU untuk meningkatkan kemampuan berpikir kritis dan motivasi belajar siswa sekolah dasar. Metode yang digunakan adalah Research and Development (R&D) dengan model ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Data dikumpulkan melalui wawancara, kuesioner, dan tes. Efektivitas media diuji menggunakan desain kuasi-eksperimen dengan kelompok kontrol non-ekuivalen. Hasil penelitian menunjukkan bahwa media pembelajaran matematika berbasis AR dengan Assembler EDU valid secara teknis dan pedagogis serta efektif dalam meningkatkan kemampuan berpikir kritis dan motivasi belajar siswa sekolah dasar. Validasi ahli menunjukkan media layak digunakan dengan revisi minor, dan uji efektivitas membuktikan keunggulan signifikan dibandingkan metode konvensional. Penggunaan AR memungkinkan visualisasi konsep bangun ruang secara interaktif, mendukung proses identifikasi dan klarifikasi konsep matematika, serta menciptakan pengalaman belajar yang menarik. Kesimpulannya, integrasi teknologi AR dalam pembelajaran matematika merupakan solusi inovatif untuk meningkatkan literasi numerasi serta menjawab tantangan pembelajaran abad ke-21 di sekolah dasar. Kata Kunci: augmented reality; media pembelajaran Matematika; motivasi belajar; pemikiran kritis; pendidikan dasar